The branding narrative of "Indonesia Spice Up The World" through the participation of the Indonesian diaspora in South Korea as brand ambassadors - Septyana, Virgitta; Saragih, Ruth Putryani (Bricolage : Jurnal Magister Ilmu Komunikasi, 2024)
The "Indonesia Spice Up the World" program is a government initiative within the creative economy sub-sector aimed at enhancing the marketing of Indonesian spice and processed food products. The involvement of diaspora communities in this program is expected to create extensive business opportunities, generate employment, contribute to foreign exchange earnings, and foster an entrepreneurship mindset, particularly among the diaspora in South Korea, which has proven to possess a significant diaspora strength. This research utilizes the conceptual framework of national branding, which includes Brand Identity, Brand Image, Brand Purpose, and Brand Quality. These concepts are used to analyze how the branding narrative "Indonesia Spice Up The World" is constructed through the involvement of the Indonesian diaspora in South Korea as brand ambassadors. The primary objective of this research is to explore how the branding narrative of "Indonesia Spice Up the World" is constructed with the involvement of Indonesian diaspora in South Korea as brand ambassadors. The conceptual framework used in this study pertains to nation branding, including Brand Identity, Brand Image, Brand Purpose, and Brand Quality. The research method employed is qualitative with an exploratory case study approach, gathering primary data through interviews with relevant parties, including the Indonesian Embassy in Seoul, Visit Indonesia Tourism Officer (VITO), and representatives of the Indonesian diaspora in Seoul as business actors. From observation and interviews, it was found that the involvement of the diaspora in supporting the narrative branding "Indonesia Spice Up The World" has not been maximized. This is due to several challenges and obstacles in program implementation. Collaboration between the government and the diaspora is considered crucial to ensure that the promotion of Indonesian spice excellence resonates effectively with other countries. Additionally, this research also highlights the importance of integrating service systems, bureaucratic reforms, mental revolutions, cross-sectoral and regulatory synchronization, human resource quality, work culture, infrastructure, facilities, national values, and philosophical principles as strengtheners in building the Indonesian national brand.